2012
DOI: 10.1063/1.4749415
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of sub-stoichiometric hydrogenated silicon oxide films for surface passivation of crystalline silicon solar cells

Abstract: Thermal stability of passivating layers in amorphous/crystalline silicon (a-Si/c-Si) heterojunction solar cells is crucial for industrial processing and long-term device stability. Hydrogenated amorphous silicon (a-Si:H) yields outstanding surface passivation as atomic hydrogen saturates silicon dangling bonds at the a-Si/c-Si interface. Yet, a-Si surface passivation typically starts to degrade already at annealing temperatures in the range of 200 to 250 °C depending on annealing time, and optical absorption i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…31,32 Here, for an increasing CO 2 /SiH 4 ratio, a clear decrease of the high-temperature peak signal and a simultaneous increase of the low-temperature peak signal is observed, pointing to increased porosity. Similar results have been reported by Einsele et al 20 With TDS and FTIR measurements, they showed that by adding oxygen to the layer its microstructure is changed significantly. For higher oxygen contents, they observed an increase in the stretching mode at 2100 cm…”
Section: A Passivation Properties Of I A-sio X :Hsupporting
confidence: 80%
See 1 more Smart Citation
“…31,32 Here, for an increasing CO 2 /SiH 4 ratio, a clear decrease of the high-temperature peak signal and a simultaneous increase of the low-temperature peak signal is observed, pointing to increased porosity. Similar results have been reported by Einsele et al 20 With TDS and FTIR measurements, they showed that by adding oxygen to the layer its microstructure is changed significantly. For higher oxygen contents, they observed an increase in the stretching mode at 2100 cm…”
Section: A Passivation Properties Of I A-sio X :Hsupporting
confidence: 80%
“…Widebandgap doped amorphous silicon oxide layers with nanocrystallites (nc-SiO x :H) are used in thin-film silicon tandem solar cells as window layers and intermediate reflectors 16,17 showing the potential for improved light management. In SHJ devices, intrinsic amorphous silicon oxide (a-SiO x :H) as well as doped nc-SiO x :H layers were tested as passivation and charge-carrier collection layers, respectively, and promising results were reported on p-type [18][19][20] and n-type crystalline silicon wafers. However, a direct comparison of such layers to state-of-the-art a-Si:H films has been lacking so far, making an assessment of their true potential difficult.…”
Section: Introductionmentioning
confidence: 99%
“…It should be mentioned, that the solubility of H 2 , which is the most favorable configuration of not bonded H that cannot be detected by FTIR, is very low in c-Si. In addition, it is known from a-SiO X :H films that the presence of H 2 is negligible as compared to bonded H, except for a-SiO X :H films with an increased amount of voids that can host H 2 molecules [16]. Additionally, it should be noted that no Si-C related peaks were found in the FTIR spectra of the deposited films, even though CO 2 was used as the oxygen source.…”
Section: (A)-(d)mentioning
confidence: 96%
“…To further decrease the short-wavelength losses, it is thus required to seek for alternatives to the standard a-Si:H layer. Possible approaches include wide-bandgap materials such as a-SiO x :H [9], [58], indirect bandap materials such as μc-Si:H [59] and perhaps the use of black silicon surfaces passivated by atomiclayer deposited aluminum oxide [60], [61]. Recently, Wan et al [62] also demonstrated PECVD a-SiN x :H layers featuring parasitic absorption less than 0.1 mA/cm 2 and excellent surface passivation.…”
Section: Further Short-circuit Current Improvementsmentioning
confidence: 99%